The Influence of Digital Technology on Financial Management - Budiasih, Yanti (Accounting Studies and Tax Journal (COUNT), 2024)
This research investigates the impact of digital technology on financial management through a systematic literature review approach. Digital transformation has triggered significant changes in business paradigms, presenting new opportunities and challenges. In the context of financial management, the use of digital payments, artificial intelligence and big data analysis is becoming the new norm. This systematic literature review details the positive effects of digital technology on daily transactions, strategic decision making, and highlights challenges such as data security and changing business models. These findings identify a knowledge gap in the literature, providing a need for further research. These results convey deep insights for practitioners and researchers, guiding the adaptation of policies and strategies in the era of digital transformation.